2016
DOI: 10.1016/j.diagmicrobio.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of molecular typing methods for the analyses of Acinetobacter baumannii from ICU patients

Abstract: Acinetobacter baumannii has emerged as an important cause of healthcare-associated infections causing great morbidity and mortality. Despite its clinical importance, it is still unknown which molecular typing method is the best to determine or confirm institutional outbreaks as well as to identify epidemiologically related isolates from different geographical areas. To determine the most discriminatory molecular typing method, we isolated A. baumannii from perianal swabs collected from intensive care unit (ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In addition, there were singletons: ST1980 and those representing the six new STs. Our findings are supported by previous studies that have shown that PFGE typing is more discriminatory than MLST typing or eBURST analysis [37].…”
Section: Plos Onesupporting
confidence: 91%
“…In addition, there were singletons: ST1980 and those representing the six new STs. Our findings are supported by previous studies that have shown that PFGE typing is more discriminatory than MLST typing or eBURST analysis [37].…”
Section: Plos Onesupporting
confidence: 91%
“…There are some limitations for this study. The first is the inclusion criteria of Acb complex strains, it has been demonstrated that a single patient may have more than one genetic type of Acinetobacter [ 42 , 43 ]. To avoid the problem of duplicate data, this study adopted a simple inclusion method of allowing only a single isolate per patient.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to minor differences in the MLVA protocol employed, but may also be explained by the knowledge that individual VNTR loci can evolve rapidly. We used gel electrophoresis in our study, a method that inherently includes a manual reading and is thus associated with greater variation in the results compared to the high precision offered by capillary electrophoresis [38].…”
Section: Discussionmentioning
confidence: 99%